Distributed innovation processes (DIPs) and the dynamics of knowledge tradability - Sally Gee (The University of Manchester, Manchester Business School, 2010)
This paper draws on two extensive case studies to explore how the co-production and exchange of knowledge is organised during innovative activity. In the empirical cases multiple, transient innovation systems emerge, and self organise, around a particular problem. The emergence and evolution of these innovation systems involves the mutual intrapenetration of market and non-market forms of exchange. The cases suggest that economic markets and knowledge acquisition networks are not alternative forms of economic organisation but are co-dependent and mutually embedded.
Keywords: 330; markets; networks; evolution; innovation; systems